FEASIBILITY ANALYSIS OF EARTHWORM AGRIBUSINESS (Lumbricus rubellus) BY CV RAJ ORGANIK IN MALANG CITY - Tarisa Tarisa; Effy Yuswita; Dina Novia Priminingtyas; Mofit Jamroni (UPT Publication and Journal Management, Islamic University of Kalimantan, 2024)
This study addresses the limited recognition of earthworm farming and the lack of detailed financial record-keeping and feasibility analysis within the business. The research aims to evaluate the revenue and income of CV RAJ Organik and assess the financial feasibility of its earthworm agribusiness. Conducted in Sukun District, Malang City, from February to April 2024, the study involved the business owner and financial manager, who provided insights into the company’s financial operations. The analysis employed includes revenue and income evaluation, followed by a financial feasibility assessment using Net B/C, NPV, IRR, and PP criteria. The results indicate that earthworm farming is profitable, with the financial analysis confirming the business's viability. The study recommends that the company maintain its financial management practices, as they meet the necessary feasibility criteria, ensuring the long-term sustainability and success of the agribusiness.